Implementasi Kurikulum 2013 (Pembelajaran PAI di SMA Negeri 1 Tungkal Jaya Kabupaten Musi Banyuasin) - Ajmain Ajmain; Abdullah Idi; Abdurrahmansyah Abdurrahmansyah (Bahasa Indonesia, Bahasa English, 2019)
This research is entitled "Implementation of the 2013 Curriculum: (PAI learning in SMA Negeri 1 Tungkal Jaya)". This study was written to determine the learning process of PAI in SMA Negeri 1 Tungkal Jaya in the application of the 2013 curriculum. This study used a qualitative descriptive approach that was evaluative. In this research, theoretical and empirical studies are conducted, both studies are very important and necessary, both of which bridge the realization of the research. This research takes a case study in SMA Negeri 1 Tungkal Jaya with data collection tools: interviews, observations and documentation with phenomenological analysis with the stages of reduction, display and verification, through technical triangulation and source triangulation. The results of this study suggest that the implementation of the 2013 curriculum in PAI learning at SMA Negeri 1 Tungkal Jaya goes through several stages, namely: First: Planning stages, where teacher make PAI lesson plan that include annual programs, semester programs, syllabus and lesson plan (RPP) which includes KI-KD, subject matter, the time allocation. Second: Stages of the implementation of learning. Learning carried out by PAI teachers emphasizes practice more than just theory, because the approach used is the 2013 curriculum scientific approach. Third: Stages of evaluation and evaluation, the assessment carried out is the assessment of spiritual attitudes, social attitudes, knowledge and skills.